การพัฒนาระบบสารสนเทศเพื่อการประกันคุณภาพการศึกษา โรงเรียนตำรวจตระเวนชายแดน - เพียงอาภา แดงสระน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purposes of this research were to study, develop and evaluate effectiveness of information system for quality assurance in education for border patrol police schools. The research method included (1) document analysis (2) a field study of 2 border patrol police schools (3) a development of the information system and computer program for implementing the information system and (4) an experimentation the information system in border patrol police schools. The findings were as follow : 1. The data for quality assurance in education were classified into 4 area, they were 1) school data included school site, vision, community characteristic, the number of teachers, the number of students, the number of students who were and were not able to continue education and the number of the students who used the library 2) teacher data included the data of personal, family, education, application to be government officer, training/visiting, work load and honorability 3) student data included the data of personal, family, health, learning achievement, abilities, skills, interests and Royal Princess’s project activities 4) teaching process information included school’s project and resource persons. 2. The information system for quality assurance in education for border patrol police schools was developed by using Microsoft Access’ 2000. The system was able to store, process, present the data and the report to explain quality of education by a microcomputer. 3. Evaluation results indicated that the information system was effective for quality assurance in education for border patrol police schools because the school was able to manage the database and information system with the accuracy, completeness, relevancy and convenience. The reports were useful to communicate with the other organizations for the education development of border patrol police schools